Manajemen dan Partisipasi Masyarakat pada Pengelolaan Kurikulum dalam Meningkatkan Mutu Pembelajaran: Management and Community Participation in Curriculum Management in Improving the Quality of Learning - Aditya, Viedy Dimas (STAI Publisistik Thawalib Jakarta, 2024)
The research aims to explain and describe curriculum management and community participation in the management of the curriculum of Al Wafi Islamic Boarding School Bogor Junior High School. The research method used is qualitative through a case study. Data collection is conducted through interviews, observations, and documentation. Data validity is ensured through triangulation and confirmability, while data management is carried out through data reduction, data presentation, and conclusion drawing. The research findings explain that curriculum management is carried out through several stages: school-specific curriculum planning through meetings attended by stakeholders and the education department, organizing by grouping national and school-specific curricula, implementation through effective and active learning, and curriculum evaluation through daily assessments, self-assessment tests, mid-semester exams, and school exams. Meanwhile, community participation in the curriculum takes the form of providing suggestions and supporting the implementation of school programs.